At home in preschool care? Childcare policy and the negotiated spaces of educational care - Gallagher A (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD)
Concerns have been raised across a range of discplinary perspectices about the heightened policy expectations which are being placed on the educational outcomes of preschool services leading to suggestions of over formalisation of the preschool space. In light of these concerns, this paper will explore how new socio-economic expectations around educational care are actually shaping the preschool space. By doing so I will argue that concerns over the formalisation of educational care need to be considered with reference to the different contexts and sectors in which educational care is being provided. In offering a more situated analysis, formalisation processes can be seen as highly contingent, as they are articulated within existing social norms around the care of young children. © 2013 Copyright Taylor and Francis Group, LLC.
This is an Accepted Manuscript of an article published by Taylor & Francis in Children's Geographies on 25 March 2013, available online: http://www.tandfonline.com10.1080/14733285.2013.779447
Keywords: Social Sciences; Geography; GEOGRAPHY; Ireland; childcare policy; educational care; preschool space; homeliness; BUILDING SCHOOLS; PAID WORK; FUTURE; GEOGRAPHIES; ASPIRATION; PROMISE; GENDER; STATE; WOMEN; UK; 1205 Urban and Regional Planning; 1604 Human Geography; 1607 Social Work